Respostas
respondido por:
1
Resposta:
Explicação passo-a-passo:
Solução:
3 - {-5 - [8 - 2 + (-5 + 9)]} =
3 - {-5 - [8 - 2 + (4)]} =
3 - {-5 - [8 - 2 + 4]} =
3 - {-5 - [6 + 4]} =
3 - {-5 - [10]} =
3 - {-5 - 10} =
3 - {-15} =
3 + 15 = 18
respondido por:
0
Oi tudo bem?
Vamos lá!!!!
3 - { - 5 - [ 8 - 2 + ( - 5 + 9 ) ] }
3 - { - 5 - [ 8 - 2 + 4 ] }
3 - { - 5 - 10 }
3 + 15
18
Espero ter ajudado
Não esqueça de adicionar como melhor resposta
Perguntas similares
4 anos atrás
4 anos atrás
4 anos atrás
7 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás